Various classes of removable partial dentures: A study of prevalence among patients attending a dental and educational institute in Riyadh, Saudi Arabia - Nadia Al-Angari; Saeed Algarni; Anas Andijani; Abdulwahab Alqahtani (Saudi Dental Journal)
Purpose: Knowledge about the most prevalent types of Kennedy classifications is of great value and will enlighten dental students, dental technicians, and practitioners regarding the treatment needs of their patients, ultimately leading to better treatment outcomes. The aim was to determine the prevalence of various Kennedy classifications among patients attending clinics at the College of Dentistry at King Saud bin Abdulaziz University for Health Sciences and King Abdulaziz Dental Center, National Guard Health Affairs, who were seeking treatment for partial edentulism. Methods: An observational cross-sectional study was conducted by visualizing cast models for partially edentulous patients. Kennedy classification, age, gender, and treatment design were recorded from the lab request sheets that were attached to the casts in the labs at both the College of Dentistry at King Saud bin Abdulaziz University for Health Sciences and King Abdulaziz Dental Center, National Guard Health Affairs. The statistical analyses were performed with SPSS version 20.0 utilizing frequency and Pearson’s and Spearman’s correlation tests. Results: Kennedy Class I (45.0%) was the most prevalent pattern in both dental arches, followed by Class III (26.2%). Next was Class II (23.3%), while Class IV was the least prevalent (5.4%). Conclusion: Kennedy Class I was the most noted classification in our patient population. As age increases, there is an increased tendency toward Class I and II.